Correlation between hyperemesis gravidarum risk factors and body weight of first-trimester pregnant women - Handayani, Handayani; Salsabila, Afifah; Hijriyati, Yoanita; Wulandari, Shenda Maulina (The Journal of Palembang Nursing Studies, 2024)
Background: Nausea and vomiting early in pregnancy are experienced by around 70-80% of pregnant women. If nausea and vomiting occur too often, it will become a pathological condition called hyperemesis gravidarum. Many factors trigger hyperemesis gravidarum, necessitating more in-depth research regarding the risk factors for hyperemesis gravidarum and their impact on the weight of pregnant women in the first trimester. Purpose: This study aimed to analyze the correlation between hyperemesis gravidarum risk factors and the body weight of first-trimester pregnant women in East Jakarta.  Methods: A quantitative study employing descriptive analysis and a cross-sectional case-control method was conducted, including 84 first-trimester respondents selected using targeted sampling techniques. Data collection was performed using questionnaires, and data analysis was conducted using Chi-square. Results: There is a significant relationship between the risk factor variables for severe morning sickness, namely age, occupation, history of vomiting, anemia, and the outcome, which is the measurement of pregnant women’s weight. Conclusions: There is a relationship between age, occupation, pregnancy, history of vomiting, anemia, and mild stress with the results of weight measurement of pregnant women in the first 3 months of pregnancy.